The Role of Digital Transformation in Enhancing SMEs’ Competitiveness in Emerging Economies (Universitas Kristen Indonesia Toraja, 2023)
Small and Medium Enterprises (SMEs) are vital for the economic growth of emerging economies. This paper explores the impact of digital transformation on improving the competitiveness of SMEs, focusing on the adoption of digital tools, challenges faced, and policy implications. Case studies from Southeast Asia and Latin America are used to illustrate the effects of digitalization on productivity, market expansion, and operational efficiency. The findings emphasize the need for government support and private sector collaboration to drive innovation in SMEs.